HUBUNGAN PENGETAHUAN DENGAN PERILAKU IBU MEMBERIKAN PENDIDIKAN SEKS PADA ANAK - Sulistianingsih, Apri; Widayati, Wahyu (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2016)
Cases of sexual assault on a child each year is increasing. This condition is caused by children not provided adequate sexual education by their parents. The provision of sexual education by parents can protect children from sexual violence cases. Based on the results of the survey in the village pre gumuk mas, at 20 the mother, it was found that 15 mothers feel awkward when teaching sex education to their children. It happened the possibility of a lack of knowledge of the mother so that the behavior provides less education. Objective: The study to determine the relationship of knowledge to the mother's behavior gives sex education to children. Research method: the type of research is observational analytic research with cross sectional approach. Total population of 45 students of early childhood education, then sampling is done with total samples that meet the inclusion and exclusion criteria to 32 kindergarten Dharmawanita Gumukmas Union. Instruments in this study using a questionnaire with each - each item about the 15 questions and analyzed using Pearson correlation and simple linear regression. Results: The obtained research is a significant relationship between knowledge with the mother's behavior gives sex education to children (Ï = 0.001) with the strength of the relationship r = 0.578, regression test results obtained determinant coefficient of 0.344 (low correlation). Keywords: knowledge, behavior, sex education of children